Hydrogeology : principles and practice - Hiscock, K. M. (Wiley Blackwell, 2014)
This book provides a comprehensive introduction to the study of hydrogeology. It has been updated to reflect advances in the field since 2004 and presents a systematic approach to understanding groundwater. Topics include: fundamental physical and chemical principles of hydrogeology; groundwater investigation techniques in the context of catchment processes; groundwater quality and contaminant hydrogeology; applications of environmental isotopes and noble gases in the interpretation of aquifer evolution, and on regional characteristics in the explanation of geological processes affecting past, present and future groundwater flow regimes; groundwater resources and environmental management; the role of groundwater in integrated river basin management, including an assessment of possible adaptation responses to the impacts of climate change. -- Edited summary from book.
Keywords: Hydrogeology.; elektronické knihy; electronic books